REBUTTAL ARGUMENT TO PRIMARY ARGUMENT IN SUPPORT OF PROPOSITION 99 (Tufts Archival Research Center, 2007)
Points of opposition to Proposition 99 in California. Argues that the increase in cigarette taxes will unfairly tax people with lower income, will make wealthy doctors richer and invite more crime in the form of smuggling. Asks supporters to vote no on Proposition 99.